Heterozygosity for CMT Type 4 Predicts a Severe Vincristine-induced Polyneuropathy Phenotype: A Case Report and Review of Literature. Issue 1 (January 2019) - Sy, Andrew; Cheng, Jerry; Cooper, Robert; Mueller, Lisa
Abstract : Vincristine (VCR) is a common chemotherapeutic agent used in the treatment of multiple types of pediatric tumors. VCR's adverse effects are well documented and commonly involve peripheral neuropathy via axonal degeneration. Neuropathic severity is dose-dependent, with sensory deficits occurring with as little as 4 mg cumulative dose. Severe peripheral neuropathy is generally rare, but its effects become additive when given to patients with undiagnosed hereditary peripheral neuropathy such as Charcot-Marie-Tooth. We report a case of an effect of VCR administration given to a patient who developed grade 4 neuropathy and was found to be a carrier of Charcot-Marie-Tooth disease type 4.